2014
DOI: 10.1016/j.bmcl.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new family of carbonic anhydrases in the malaria pathogen Plasmodium falciparum —The η-carbonic anhydrases

Abstract: The genome of the protozoan parasite Plasmodium falciparum, the causative agent of the most lethal type of human malaria, contains a single gene annotated as encoding a carbonic anhydrase (CAs, EC 4.2.1.1) thought to belong to the α-class, PfCA. Here we demonstrate the kinetic properties of PfCA for the CO2 hydration reaction, as well as an inhibition study of this enzyme with inorganic and complex anions and other molecules known to interact with zinc proteins, including sulfamide, sulfamic acid, and phenylbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
186
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 302 publications
(191 citation statements)
references
References 76 publications
2
186
0
Order By: Relevance
“…CAs are also found in plants, fungi, algae, protozoa, cyanobacteria and bacteria 8,[19][20][21][22][23][24][25] . Six different, genetically distinct CA families are known to date: a-, b-, g-, d-, z-and Z-CAs 8,20,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAs are also found in plants, fungi, algae, protozoa, cyanobacteria and bacteria 8,[19][20][21][22][23][24][25] . Six different, genetically distinct CA families are known to date: a-, b-, g-, d-, z-and Z-CAs 8,20,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Only the z-CA crystallized has three slightly different active sites on the same polypeptide chain 26 , whereas no X-ray crystal structures of d-and Z-CAs are available up to now. CAs contain Zn 2+ in their active site, coordinated by three histidine residues and a water molecule/ hydroxide ion (in the a-and g-CAs) or two Cys and one His residues (in the b class), with the fourth ligand being a water molecule/hydroxide ion 22,23,27 . In the Z-CAs, the coordination pattern of the Zn(II) ion is totally different from the other classes, with one Gln and two His acting as ligands 21 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5,[30][31][32][33][34][35][36][37][38] These enzymes are involved in a multitude of physiologic processes in organisms all over the phylogenetic tree, with six genetically distinct CA classes known to date: the a-, b-, c-, d-, f-and g-CAs. 26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type.…”
mentioning
confidence: 99%
“…Among them, the a-, b-, g-and d-CAs are broadly distributed in many microorganisms 1 , whereas the Z-CAs were described only in protozoa for the moment 5 . To date, two different b-CAs have been reported in Escherichia coli, the most investigated bacterium for the molecular biology viewpoint.…”
mentioning
confidence: 99%